Pengembangan Aplikasi Pencarian Pekerjaan Part-Time, Proyek, dan Penelitian bagi Mahasiswa Berbasis Website - Muhammad Nailan Nabil; Rahmadi Wijaya; Erna Hikmawati; Amru Abid Zakly; Aisyah Fadzila Hani (SISFOTENIKA, 2024)
Unemployment among undergraduate is a serious problem that has a broad impact on individuals and society. The lack of a platform that can help students gain experience and understand trends in the industrial world is one of the factors causing the high unemployment rate among undergraduates. To overcome this problem, this research developed the Boedoo application, a website-based platform that facilitates searching for part-time jobs, projects and research for students. This application was developed using the Software Development Life Cycle (SDLC) method with the Waterfall model. Through User Acceptance Testing (UAT) involving 10 Telkom University students, the Boedoo application succeeded in showing its effectiveness, with 89.6% of respondents agreeing that the existing features had been successfully implemented well. The results of this research show that Boedoo can help students gain hands-on experience in the industry, increase user engagement and satisfaction, and facilitate their transition into the job market. In this way, Boedoo contributes to reducing the unemployment rate of undergraduate graduates and increasing their competitiveness in the world of work.